Promotion Channels Adopted By the Producer/Manufacturer For Enhancing Sale of Agricultural Inputs: An examination of promotional techniques used by producers and manufacturers to increase the sales of agricultural inputs (Journal of Advances and Scholarly Researches in Allied Education, 2012)
For the purpose of exactestimation of the perceptional gap between farmers’ perception and the views ofthe practitioners, it seemed essential to collect the observations of thedealers and agency holders. Accordingly, the data has been collected from theshopkeepers/agency holders of districts Fatehabad and Ambala respectivelythrough a structured questionnaire.  Theanalysis related to marketing of cotton seeds, wheat seeds, fertilizer,pesticide and tractor has been discussed in the light of the spirit mentionedabove.